Determinants of thinness among school adolescents in Legehida district, Amhara region, north east Ethiopia: an unmatched case-control study - Ali, Awol Assen; Adugna, Dessalegn Tamiru; Ayele, Wolde Melese; Tadesse, Sisay Eshete; Mekonnen, Tefera Chane; Wudu, Muluken Amare (Frontiers in Adolescent Medicine, 2024)
Background: Adolescence is a critical stage of human growth and development, and adolescent nutritional status is a significant predictor of health outcomes. However, adolescents in developing countries, including Ethiopia, have received little attention from nutrition-related programs in recent decades. Consequently, malnutrition among adolescents is a widespread issue in these regions.The study aimed to identify the determinants of thinness among school adolescents in the Legehida district of South Wollo Zone, Northeastern Ethiopia.Methods: A school-based, unmatched case-control study was conducted from January 20 to February 2, 2019. A total of 525 school-aged adolescents (175 cases and 350 controls) from the Legehida district were enrolled using a multistage sampling technique. Data were collected through interview-administered questionnaires and anthropometric measurements. EpiData version 3.1 was used for data entry, while Anthroplus software was employed for anthropometric measurement entry and analysis. The data were then exported to SPSS version 25 for further analysis. Bivariate and multivariable logistic regression analyses were performed to assess the determinants of adolescent thinness.In this study, thinness among school adolescents was significantly associated with several factors: the absence of a latrine at home [AOR = 8.2, 95% CI (3.8, 8.17)], meal skipping per day [AOR = 3.1, 95% CI (1.2, 7.3)], inadequate consumption of fruits and vegetables [AOR = 7.5, 95% CI (3.9, 14.5)], having more than four household members [AOR = 13.6, 95% CI (7.1, 26)], and the consumption of unsafe water [AOR = 7.7, 95% CI (3.8, 15.6)].The absence of latrines and access to clean water, dietary factors, and family size emerged as significant contributors to adolescent thinness in this study.Addressing the nutritional challenges faced by adolescents will require collaborative efforts across sectors.